Acute phenthoate self-poisoning: a prospective case series. (1st February 2022) - Rambabu, Lekaashree; Mohamed, Fahim; Dhanarisi, Jeevan; Gawarammana, Indika; Raubenheimer, Jacques; Mackenzie, Lorraine; Roberts, Michael S.; Buckley, Nicholas; Eddleston, Michael
Abstract: Background: The clinical characteristics following self-poisoning with organophosphorus (OP) insecticides differs according to the insecticide ingested. Phenthoate is a dimethoxy WHO Hazard Class II OP pesticide with limited literature on its clinical characteristics and outcome. We aimed to better understand its clinical characteristics by studying patients with phenthoate self-poisoning in Sri Lanka. Methods: We conducted a prospective cohort study of patients presenting with phenthoate self-poisoning to eight hospitals in Sri Lanka between 2002 and 2018. Clinical outcomes were recorded for each patient. Blood samples for measuring plasma phenthoate concentration, cholinesterase activity, and response to oximes were available for a very small number of patients recruited to a clinical trial. Results: Two hundred and ninety-two patients who ingested agricultural phenthoate formulations were included in the study. Median time to admission was 3.9 (IQR 2.4 - 6.8) h. Forty-two (14.4%) patients were intubated, mostly (30/37, 81%) within 24 h of ingestion (median time to intubation 7.2 [IQR 2.6–20.9] h). Median duration of intubation was 74.8 (IQR 26.8–232.5) h; the longest duration in a survivor was 592 h. Nineteen died (case fatality 6.5%, 95% CI 4.0–10.0); median time to death was 37 (IQR 16 - 101.7) h. Median plasma phenthoate concentration in patients with samples ( n = 81) was 135 (IQR 62.7–356.5) ng/mL (0.42 µmol/mL [0.2 to 1.1 µmol/mL]). Five of six patients receiving pralidoxime chloride 2 g showed an initial increase in AChE and BuChE activity that was not sustained despite an infusion of pralidoxime. Conclusion: Phenthoate self-poisoning has a 6.5% case fatality rate. Most patients who experience respiratory failure undergo early intubation; most deaths occurred among those patients who were intubated less than 24 h after ingestion. There was a non-sustained increase in cholinesterase activity with pralidoxime, but further studies are required to analyse the extent to which oximes are clinically effective in phenthoate self-poisoning.